Text-Fabric Dataset of the Samaritan Pentateuch. - Naaijer, Martijn; Højgaard, Christian Canu; Schorch, Stefan; Ehrensvärd, Martin (Research Data Journal for the Humanities & Social Sciences, 2024)
In this article, the authors present a dataset of the text of the Samaritan Pentateuch with word-level linguistic annotations. The Samaritan Pentateuch is an important early witness of the Pentateuch or Torah. This dataset is based on a transcription generally taken from manuscript Dublin, Chester Beatty Library 751 (Genesis 1:1–Deuteronomy 32:36) and supplemented from manuscript Nablus (Kiryat Luza), Samaritan Synagogue, Garizim 1, where the former manuscript has not preserved the text (Deuteronomy 32:36b–34:10). The dataset is a Text-Fabric dataset. Text-Fabric is a Python package for processing annotated text corpora, which means that the dataset comes with an app, where the text can be inspected and queried using the annotations. It is also easy to perform textual and linguistic research using Python scripts and to make comparisons with other relevant textual datasets with the same annotation conventions.